Reassessing the Export Competitiveness of Vietnam - Shashi Kant Chaudhary; Nguyen Viet Khoi, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In this paper, primarily the export specialisation pattern of Vietnam has been examined from the perspective of domestic value added exports. In addition, an effort has been made to identify presence of exaggeration in gross exports measures of industries level competitiveness. Empirical findings suggest that the export specialisation of Vietnam has reversed, and there is presence of exaggeration in the estimates of comparative advantage of ‘human capital and technology intensive’ industries that has also caused in ballooning up their shares in gross exports. Such pattern has arisen because intra-industry trade has become increasingly significant in Vietnam.Received 11th March 2019; Revised 17th October 2019; Accepted 20th October 2019